Enhancing celery’s growth, production, quality, and nutritional status using tryptophan and glycine amino acids - A. M. M. El-Tanahy; Sami H. Mahmoud; Mohamed S. A. Abd Elwahed; Dina M. Salama (Scientific Reports)
Abstract Finding a way to establish a sustainable cultivation system to produce celery as an important source of human being nutrition system due to its health and nutritional advantages is increasing by the day. Amino acids have a deep impact on plant metabolism; they improve mineral uptake and increase shoots and root growth, yield, chlorophyll biosynthesis, and photosynthesis rate as well as encouraging stimulation of several enzymes and coenzymes which lead to improved plant development and production besides quality. A two-year (2021/2022–2022/2023), trial was conducted to discuss two essential amino acids Glycine (GLY) and Tryptophan (TRP) effect on celery’s growth, production, photosynthetic pigments, vitamin (C), total phenols, total flavonoids, total antioxidant activity, total indoles, nutritional status, and amino acids contents. During the winter season, three levels of each amino acid (0, 50, and 75 mg/l) were sprayed in two doses after 30 days of cultivation and 15 days from the first foliar. Results showed that the best performance of amino acids on plants vegetative growth characteristics, photosynthetic pigments, biochemical constituents, yield, and amino acids content was conducted by using (GLY + TRP) mix followed by TRP then GLY, while the best level of foliar applied amino acids was 75 mg/l in concentration. The best results on celery’s vegetative growth, yield, chemical content, and amino acid content were recorded by using the (GLY + TRP) mix at the highest level of 75 mg/l in concentration.